Akurasi dan Fleksibilitas: Perbandingan Metode Konvensional dan Kontinu dalam Pengukuran Koefisien Muai Panjang Logam - Goenawan, Stephanus Ivan (Cylinder : Jurnal Ilmiah Teknik Mesin, 2025)
This study compares two methods for measuring the coefficient of linear expansion of metals: the Conventional (Discrete) Method and the New (Continuous) Method, focusing on effectiveness, accuracy, and flexibility. Thermal expansion is a crucial phenomenon in materials engineering, and the coefficient of linear expansion is crucial for predicting metal behavior under temperature variations to prevent structural failure. The historically dominant Discrete Method (MD) relies on the linearity assumption and fundamentally requires an initial length (L0) as an absolute reference. This dependence limits flexibility in dynamic experimental situations, where subsequent measurements must reference the original L0. With the development of numerical calculus, the Continuous Method (MC) was developed based on the differential principle, where the coefficient of linear expansion can be calculated from infinitesimal changes in length and temperature without requiring an explicit L0. This approach allows measurements from any point, making it more adaptable for incremental testing. Through numerical simulations on five metals, this study evaluates both methods in two scenarios: an initial measurement of the coefficient of linear expansion and the flexibility of measurements from different temperatures. The results show that both methods produce very close linear expansion coefficient values when measured from the same initial conditions. However, MK proved much more adaptive and efficient, consistently producing valid linear expansion coefficient values without being tied to the original L0. MK can use the length data available at that time as a starting point for subsequent measurements, in contrast to MD, whose results become inconsistent if not referenced to L0. This flexibility of MK is particularly relevant for dynamic material testing and advanced experiments where initial conditions may not always be known or may change. This study presents scientific justification and practical guidance for adopting MK as a more flexible alternative in the thermal characterization of modern materials.